"Molecular dynamics comparative study on properties of different fiber-reinforced nitrile rubbers" - SU Yu-hao1, LI Yun-long1, WANG Shi-jie1, NIE Rui2 (Hecheng xiangjiao gongye)
Fiber surface model and composite model were constructed by molecular dynamics si-mulation, the interfacial bonding performance and mechanical properties of the composites were tested by fiber pull-out simulation and transverse tensile simulation, the interfacial interaction between diffe-rent fibers and nitrile rubber (NBR) matrix was analyzed from a microscopic perspective, the reinforcement effects of glass fiber (GF), basalt fiber (BF) and polyethylene fiber (PE) on the NBR matrix were compared, and the mechanism affecting the interface bonding performance was discussed. The results indicated that the interfacial interaction between GF and NBR matrix was the strongest, and GF could adsorb the most NBR molecular chains during the pull-out process, followed by BF, but there was little difference between GF and BF, while the interfacial interaction between PE and NBR matrix was the wea-kest, and the problem of insufficient tear resistance of the composites could be solved by the addition of GF. For BF/NBR composite, the higher strength of BF itself could better enhance the mechanical pro-perties of the composite in the fiber direction, and in engineering applications, BF could be arranged along the direction of external force to enhance the ability of the composite to resist deformation failure.